Air Crash And Pressure (Global Journal of Science Frontier Research, 2023)
This paper studies hat air crash would be caused by the difference of pressures between outside and inside of passenger s cargo Such difference of pressures can break the window or door and thus make the plane to crash In order to calculate the pressure outside passenger s cargo this paper set up and solves the solution of three type equations A w T eq B w - P eq and C J - P eq The A type is the base It states that the derivative of wind speed respect to time proportions to the derivative of temperature respect to track space The A s solution obtained by method of separating variables has been checked by weather forecasting by dimensional check and by other model check The solutions of B and C can be obtained directly from A Missing plane MH370 has been used as an example to show the calculation of pressure outside the passenger s cargo This paper would be referenced to pilot administrator engineer scientist teacher and student
Keywords: boyles law; charles’ law; wind speed – temperature equation; wind speed – pressure/density equation